2020
DOI: 10.1021/acs.jpca.0c01260
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nonvalence States in the Ultrafast Dynamics of Isolated Anions

Abstract: Nonvalence states of neutral molecules (Rydberg states) play important roles in nonadiabatic dynamics of excited states. In anions, such nonadiabatic transitions between nonvalence and valence states have been much less explored even though they are believed to play important roles in electron capture and excited state dynamics of anions. The aim of this Feature Article is to provide an overview of recent experimental observations, based on time-resolved photoelectron imaging, of valence to nonvalence and nonv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 108 publications
1
35
0
Order By: Relevance
“…Recent timeresolved photoelectron spectra revealing the involvement of DBSs in the electronic relaxation of analogues of the photoactive yellow protein chromophore 77 have led to the suggestion that non-valence states may play an important role in the electronic relaxation mechanisms of other biochromophore anions in the gas phase. 76 This work supports this idea and shows how the involvement of non-valence states can be identified from frequency-resolved photoelectron spectroscopy measurements following photoexcitation of higher lying electronic states. To determine the timescales of the relaxation process and the key vibrational modes will require time-resolved photoelectron spectroscopy measurements and quantum dynamics calculations, which we plan to do.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Recent timeresolved photoelectron spectra revealing the involvement of DBSs in the electronic relaxation of analogues of the photoactive yellow protein chromophore 77 have led to the suggestion that non-valence states may play an important role in the electronic relaxation mechanisms of other biochromophore anions in the gas phase. 76 This work supports this idea and shows how the involvement of non-valence states can be identified from frequency-resolved photoelectron spectroscopy measurements following photoexcitation of higher lying electronic states. To determine the timescales of the relaxation process and the key vibrational modes will require time-resolved photoelectron spectroscopy measurements and quantum dynamics calculations, which we plan to do.…”
Section: Resultssupporting
confidence: 74%
“…The fact that they are almost identical in all the photoelectron spectra recorded over this reasonably wide range of photon energies suggests that they must arise from detachment from an electronically excited state whose potential energy surface is parallel to that of the neutral, such as a weakly bound non-valence state. [74][75][76] This is likely to be a dipole-bound state (DBS) due to the high dipole moments of the M-phenolate-enol and M-phenol-enolate neutral radicals (5.4 D and 6.0 D, respectively, for the trans forms) which are large enough to bind electrons.…”
Section: Discussionmentioning
confidence: 99%
“…S C H E M E 2 Overview of the formation pathways of radical Breslow intermediates than 1.625 D under Born-Oppenheimer approximation (or ≥2.5 D in experiments) may pronounce a DBS when binding with an excess electron. [20] A molecule in the DBS could convert into a valence-bound state (i.e., the conventional excited state), or form a stable valence state by the detachment of an electron. Examples for DBS include carbon dioxide anion, [19d] nitromethane, [21] and acrylonitrile.…”
Section: S C H E M E 1 Structures and Reactivities Of Breslow Intermediatesmentioning
confidence: 99%
“…[23] Verlet and coworkers utilized photoelectron spectroscopy and investigated the dynamics of the nonvalence correlation-bound state of several anions. [20,24] They observed a valence-to-nonvalence conversion process in deprotonated para-coumaric acid (pCE À ), a model system of photoactive yellow protein chromophore. [24c] Ab initio methods have been employed to depict the anions, [19b,19c,25] while Jordan and coworkers assessed theoretical approaches to treat the nonvalence correlation-bound state and concluded that the equation-of-motion coupled-cluster with single and double excitations (EOM-CCSD), second-order algebraic diagrammatic construction (ADC(2)), and G 0 W 0 Green's function are able to appropriately describe the nonvalence correlation-bound anions.…”
Section: S C H E M E 1 Structures and Reactivities Of Breslow Intermediatesmentioning
confidence: 99%
“…Specifically, photoelectron angular distributions provide a measure of the molecular orbital from which the electron was detached, 17,18 but this orbital is of course also sensitive to the geometry of the anion. [19][20][21] Additionally, photodetachment near the detachment threshold can lead to the excitation of vibrational resonances of non-valence states, either directly 16,22 or indirectly, [23][24][25][26] which yields structure in low energy electron emission that can be correlated with vibrational modes of the final neutral state, thus offering an additional measure of structure.…”
mentioning
confidence: 99%